CrossTalk proposal: Heat acclimatization does improve performance in a cool condition - Minson, C. T.; Cotter, J. D. (The Journal of Physiology, 2016)
Repeated exposure to a hot climate (i.e. acclimatization) or artifcial environment (acclimation), hereafter collectively termed HA, elicits greater cardiovascular and thermoregulatory adaptations than are obtained by training in temperate conditions (Convertino et al. 1980; Cohen & Gisol, 1982). Endurance performance is optimized in relatively cool temperatures (?10-14°C; Ely et al. 2007a), and deteriorates with modest increases in temperature (Galloway & Maughan, 1997; Ely et al. 2007b). Regardless, heat strain is still present during strenuous exercise in cool conditions, evident by sweating and elevated skin bloodfow,and HAmay confer additional cross adaptations for exercise performance. In this CrossTalk article, we present evidence supporting the case that HA is ergogenic in certain individuals and exercise settings. However, we acknowledge there are currently more questions than answers on the ergogenic utility of HA - including many of the same questions that apply to hypoxic/altitude training despite the longer interest in that stressor as an ergogenic training aid.